Panel Data Regression: Equity Financing and Debt-based Financing Islamic Commercial Banking in Indonesia - Isnaini Ulfa Rinda Sari; Rofiul Wahyudi (University of Darussalam Gontor, 2023)
This paper investigates the impact of equity financing and debt-based financing on profitability in Islamic Commercial Banks. Panel data regression is used to determine the effect of equity-based financing and debt-based financing on Islamic commercial banks' profitability in Indonesia. The data used in this study are the aggregate financial statements of Islamic commercial banks during 2015-2019. The research findings show that partially debt and equity-based financing does not affect ROA and ROE of Islamic Commercial Banks. However, simultaneously the statistical results show a difference where debt and equity-based financing do not affect ROA. Meanwhile, debt and equity-based financing simultaneously affect ROE